PENGARUH TAMBAHAN PENGHASILAN PEGAWAI TERHADAP KINERJA DINAS PEKERJAAN UMUM DAN TATA RUANG KABUPATEN KEPULAUAN TALAUD - UMBEANG, FRIDEL; RORONG, ARIE; PLANGITEN, NOVVA (Sam Ratulangi University, 2020)
With the fulfillment of the needs of the employees and family life through salary, benefits, and the like,it will in turn encourage them to improve the performance of work. On the basis of the problem of thisresearch aims to know the additional influence of employees ' income to performance at the PublicWorks Department and the Talaud Islands regency.This type of research is quantitative research. Quantitative research can be interpreted as a researchmethod based on positivism philosophy, used to research on certain populations or samples. The dataanalysis technique used in this study is a simple regression analysis techniqueThe results showed that there was an additional influence on employees ' income to the performance ofemployees at the Public Works Department and the Talaud Islands district. The amount of employeeincome contributions to the performance of employees at the Public Works Office and the RegionalSpatial planning of Talaud Islands is 87.34% and the remaining 12.66% is influenced by other variablesnot examined in this study. The results of this study stated that there was a relationship betweenemployee income supplement to employee performance so that it could affect employee performance.Keywords: additional income, employees, performance